Peran pesantren dalam memperbaiki moral pada generasi milenial - Hafidh, Ahmad Nur (Maliki Interdisciplinary Journal, 2025)
In the current era, morality is something that every human being needs to have. Therefore, there is a need for moral provision, especially for the millennial generation who will become the nation's successors. One of them is Islamic boarding schools as a medium of education and moral formation in the millennial generation that the failure of moral development is one of the many factors that have the potential for naughty teenagers to appear, one of which is the lack of parental supervision in fostering their children. With moral education in Islamic boarding schools, it is hoped that this will improve the morale of the generation. Millennials are getting better than before. Islamic boarding schools (pesantren) play a strategic role in shaping the character and morals of the younger generation through an educational approach grounded in religious values. Within the pesantren environment, students not only acquire religious knowledge but are also guided to instill the values ​​of honesty, discipline, responsibility, and social awareness in their daily lives. Habituating religious activities such as congregational prayer, Quran recitation, and ethical social interaction are essential components of the student's personality development process. With an educational system that integrates knowledge and morals, pesantren are expected to serve as moral bulwarks for the millennial generation amidst the increasingly rapid flow of globalization and technological advancement. Through character education based on Islamic values, it is hoped that the younger generation will grow into individuals with noble character and integrity, capable of making positive contributions to society and the nation.